The SEC’s Short-Sale Experiment: Evidence on Causal Channels and Reassessment of Indirect Effects - Black, Bernard S.; Desai, Hemang; Litvak, Katherine; Yoo, Woongsun; Yu, Jeff Jiewei (Management Science, 2024)
During 2005–2007, the Securities and Exchange Commission conducted a randomized trial in which it removed short-sale restrictions from one third of the Russell 3000 firms. Early studies found modest market microstructure effects of removing the restrictions but no effect on short interest, stock returns, volatility, or price efficiency. More recently, many studies have attributed a wide range of indirect outcomes to this experiment, mostly without assessing the causal channels for those outcomes. We examine the three most often cited causal channels for these indirect effects: short interest, returns, and managerial fear. We find no evidence to support these channels. We then reexamine the principal findings in four recent studies using a sample that closely matches the actual experiment and a common research design and find minimal support for the reported indirect effects. Our findings highlight the importance of confirming a causal channel or an economic mechanism and show that sample selection and specification choices can produce statistical significance even without an underlying economic mechanism. This paper was accepted by David Sraer, finance. Supplemental Material: The internet appendix and data are available at https://doi.org/10.1287/mnsc.2023.4918 .